What more can you do with Koha? / Amzari Abu Bakar … [et al.] - Abu Bakar, Amzari; Rahmad, Fadhilnor; Mohd Amin, Zahari; Mustaffar, Mohd Yusof; Bunawan, AP Azli (Faculty of Information Management, 2015)
Koha is an Open Source Integrated Library Systems was developed in 1999. Koha has been adopted by libraries in Malaysia starting in 2008. After 7 years, Koha has been chosen by significant numbers of libraries in Malaysia including large academic library recently. To date there are more than 19 academic libraries using Koha nationwide. The trend gives indication of library acceptance in Open Source Software as compared to other Open Source ILS Software. Due to the trend, this paper intends to discuss post implementation of Koha Open Source ILS in two perspectives; things that might be missed and new suggested features that can be implemented with Koha and using other open source components. This paper gives overview of selected features that might be missed by Koha users, and what more can be done with the system.